FACTORS OF CONFLICT BETWEEN BOKO HARAM AND THE GOVERNMENT OF NIGERIA IN 2009-2014 - Theo Dhewo Tondo Widigdo (HI 16 UMY 178, 2016)
*178 Boko Haram was emerged in 2002 named Jama'atu Ahlis Lidda'Awati Wal-Sunna, firstly established as a peaceful group known for education. In 2009, the group started its uprising against the government of Nigeria. The international world shocked when in 2011 the group attacked UN compound in Abuja as the first attack on international actor and in 2014 the group kidnapped about 276 teenage girls from a school in Chibok, increasing the concern from the international world. The conflict continue and escalating, involving another international actors such as another terrorist groups and states; Chad, Cameroon and Niger. The questions emerged when Nigeria is considered as the biggest country in African continent and one of the most populous countries in the world. Nigeria has a large amount of natural resources which is oil discovered back then in 1950s. While tax is not the largest income for Nigeria, the most prominent income for the state is the income resulted from the oil. Thus the factors of conflict between Boko Haram and Government of Nigeria are questioned. This paper will analyze the factors of the conflict between Boko Haram and the government of Nigeria from 2009-2014. It involves the theory of conflict causes as the tool to find the factors. First, this paper will prove that condition has already prone to conflict because of weak state, unjust political institutions, and massive economic problems. Second it will prove that the conflict eventually triggered by three triggers, one primary trigger which is bad leaders in Boko Haram and the Government of Nigeria and two secondary triggers which are bad domestic problems of Nigeria and African region as Bad Neighborhoods of Nigeria.